2019
DOI: 10.1371/journal.pone.0223533
|View full text |Cite
|
Sign up to set email alerts
|

The trigger-information-response model: Exploring health literacy during the first six months following a kidney transplantation

Abstract: The main objective of this study was to explore how kidney transplant recipients find, understand, and use health information, and make decisions about their health—also known as health literacy. Kidney transplant recipients must take an active part in their health following the transplantation, since a new organ requires new medication and focus on lifestyle to prevent side-effects and signs of organ rejection. Consequently, it is of major clinical relevance to explore how kidney transplant recipients underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Previous studies with CKD patients have reported similar findings; for example, an Australian qualitative study characterized CKD patients either as receivers (passively seeking) or engagers (actively seeking) of health information [ 34 ]. In addition, a recent study exploring HL in Norwegian kidney recipients found that the patients fluctuated between different phases in their efforts to balance the amount of information they accessed, suggesting that they needed to be triggered by a symptom or concern to search for health information [ 35 ]. Based on our findings and earlier research [ 34 , 35 ], we suggest that limiting the input of health information might be a strategy for some individuals to cope with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with CKD patients have reported similar findings; for example, an Australian qualitative study characterized CKD patients either as receivers (passively seeking) or engagers (actively seeking) of health information [ 34 ]. In addition, a recent study exploring HL in Norwegian kidney recipients found that the patients fluctuated between different phases in their efforts to balance the amount of information they accessed, suggesting that they needed to be triggered by a symptom or concern to search for health information [ 35 ]. Based on our findings and earlier research [ 34 , 35 ], we suggest that limiting the input of health information might be a strategy for some individuals to cope with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study exploring HL in Norwegian kidney recipients found that the patients fluctuated between different phases in their efforts to balance the amount of information they accessed, suggesting that they needed to be triggered by a symptom or concern to search for health information [ 35 ]. Based on our findings and earlier research [ 34 , 35 ], we suggest that limiting the input of health information might be a strategy for some individuals to cope with CKD. The current study revealed that some patients deliberately choose to avoid health information; therefore, providing more information or simplifying existing information might not always be the solution to increase HL.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a new project to investigate health literacy in the context of renal transplantation. In this project, patients reported a need to be more thoroughly prepared for their transplantation, in order to make use of health information relevant to their life and situation [17,18]. Consequently, a new health communication intervention was developed.…”
Section: Introductionmentioning
confidence: 99%